2017
DOI: 10.1093/mnras/stx239
|View full text |Cite
|
Sign up to set email alerts
|

LOFAR observations of decameter carbon radio recombination lines towards Cassiopeia A

Abstract: We present a study of carbon radio recombination lines towards Cassiopeia A using LO-FAR observations in the frequency range 10-33 MHz. Individual carbon α lines are detected in absorption against the continuum at frequencies as low as 16 MHz. Stacking several Cα lines we obtain detections in the 11-16 MHz range. These are the highest signal-to-noise measurements at these frequencies. The peak optical depth of the Cα lines changes considerably over the 11-33 MHz range with the peak optical depth decreasing fro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 61 publications
1
41
0
Order By: Relevance
“…The gas properties derived from the CRRL analysis seem to bridge the gap between the atomic gas traced by the 21 cm line of HI and the molecular gas traced by the CO lines in the millimimeter (Oonk et al 2017;Salas et al 2017). From spatially unresolved observations of the 21 cm-HI line in this direction Davies & Matthews (1972) derived a temperature of 140±40 K for the two most prominent Perseus arm absorption features at −47 and −38 km s −1 .…”
Section: Envelopes Of Molecular Cloudsmentioning
confidence: 82%
See 2 more Smart Citations
“…The gas properties derived from the CRRL analysis seem to bridge the gap between the atomic gas traced by the 21 cm line of HI and the molecular gas traced by the CO lines in the millimimeter (Oonk et al 2017;Salas et al 2017). From spatially unresolved observations of the 21 cm-HI line in this direction Davies & Matthews (1972) derived a temperature of 140±40 K for the two most prominent Perseus arm absorption features at −47 and −38 km s −1 .…”
Section: Envelopes Of Molecular Cloudsmentioning
confidence: 82%
“…In order to model the gas properties we assume that the radiation field the gas is immersed in is constant. Since we are studying gas on scales of 1 pc and the gas is at a distance of 220 pc from Cas A (e.g., Kantharia et al 1998;Salas et al 2017), the possible contribution of Cas A to the radiation field (Stepkin et al 2007) will change by a negligible amount over the observed structure. Additionally, there are no other known strong, low-frequency, discrete radiation sources in the field.…”
Section: Physical Conditions From Crrlsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Perseus Arm component centered at -47 km s −1 has been treated in the literature as a single component gas cloud (e.g. Kantharia et al 1998b;Salas et al 2017) whereas the maps presented in figure 4 show evidence for significant spatial and spectral sub-structure. To investigate further the nature of these components we split the emission over the face of Cas A into three parts along the lines shown in the right panel of figure 5 covering (i) The western part of the bridge, (ii) The eastern part of the bridge, (iii) Emission north of the bridge.…”
Section: Evidence For Multi-component Gasmentioning
confidence: 99%
“…Observations of CRRLs have spanned frequencies of 10 to over 5 000 MHz (Payne et al 1994;Roshi, Goss, & Jeyakumar 2014;Salas et al 2017). Peters et al (2010) summarised the information about known Galactic low-frequency CRRLs and, using a modified version of the radiometer equation, calculated the approximate amount of observing time required in order for the new generation of low-frequency telescopes to detect them.…”
Section: Turn-over Frequency Of Crrl Sourcesmentioning
confidence: 99%